Prezygotic isolation confirms the exclusion of Triatoma melanocephala, T. vitticeps and T. tibiamaculata of the T. brasiliensis subcomplex (Hemiptera, Triatominae) - Santos Neves, Joao Marcos dos [UNESP]; Sousa, Paulo Sergio de [UNESP]; Oliveira, Jader de [UNESP]; Ravazi, Amanda [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Reis, Yago Visinho dos [UNESP]; Bortolozo de Oliveira, Ana Beatriz [UNESP]; Pinotti, Heloisa [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; Rosa, Joao Aristeu da [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP] (Elsevier B.V., 2020)
Chagas disease is caused by the Trypanosoma cruzi and transmitted mainly by triatomines. Triatoma is a paraphyletic group and the species of this genus are grouped into complexes and subcomplexes. Morphological data and geographical distribution grouped initially T. melanocephala, T. vitticeps and T. tibiamaculata in the T. brasiliensis subcomplex. However, karyotypic and phylogenetic analysis suggested the exclusion of T. melanocephala, T. vitticeps and T. tibiamaculata from this subcomplex. Considering that studies of experimental crosses can help to understand the systematics of species, we performed experimental crosses between T. melanocephala, T. vitticeps and T. tibiamaculata with T. b. brasiliensis. No crosses resulted in hybrids. Taking into account that the species of the T. brasiliensis subcomplex do not present interspecific prezygotic barriers, the characterization of reproductive barriers shows that T. melanocephala, T. vitticeps and T. tibiamaculata do not present an evolutionary proximity relationship with the species of this subcomplex. Thus, we confirmed the exclusion of these species from the T. brasiliensis subcomplex and we emphasize the importance of experimental crosses for evolutionary studies.
Keywords: Chagas disease vectors; Systematics; Reproductive isolation